Effect of use of non - cash payment in the digital era of business - Dede Suleman (Institute of Computer Science (IOCS), 2023)
Study This aim For know How influence use QRIS cashless payments to entrepreneur in the digital age. It is important to conduct this research so that we can find out whether promoting the use of digital money is appropriate. Methodology research used, with _ approach descriptive quantitative. Sample in study This consists of 110 respondents with use technique data collection with spread questionnaire via Google forms. Statistical data processing techniques done with using (SPSS). Found that impactful use of digital QRIS significant for traders. 75.4 % Implications of Actor Results Use of QRIS for Empowerment Entrepreneurs. Because matter This make it easy for do transaction consumer.